Modeling of the new neutron filter with 5.6 keV energy - V. A. Libman; O. O. Gritzay; S. P. Volkovetsky (Ядерна фізика та енергетика)
New filtered neutron beam with the average energy of 5.6 keV was simulated using the latest versions of the evaluated nuclear data libraries ENDF/B-VII.1 and CENDL-3.1. The main components of this new filter are: 60Ni, manganese, sulfur, and cerium oxide. Expected filter characteristics are: the average energy is 5.62 keV; neutron line width at half maximum is 1.73 keV; the purity of the main line is 84 %; the neutron flux is 2⋅105 n/(s⋅cm2). Experimental testing of the parameters of this new filter will be done during the next campaign of the reactor WWR-M.